The effect of organizational learning on organizational commitment, job satisfaction and work performance - Che Rose, Raduan; Samy, Naresh Kumar; Ong, Gua Pak (The Clute Institute, 2009)
The literature review reveals that there is a relationship between organizational learning organizational commitment, job satisfaction and work performance. However, it is apparent that the integrated relationships between these variables have not been found to be reported. Hence, we examine the relationship among these variables using a sample of public service managers in Malaysia. Organizational learning was found positively related to organizational commitment, job satisfaction, and work performance. Organizational commitment and job satisfaction are also positively related with work performance and these variables partially mediate the relationship between organizational learning and work performance. Implication of the study and suggestions for future research been discussed in this paper.